Sulzbacheromyces leucodontium (Basidiomycota, Lepidostromataceae), a new species of basidiolichen widely distributed in the Neotropics - Coca, Luis Fernando; Gómez Gómez, Salomé; Guzmán Guillermo, Jorge; Trujillo Trujillo, Edwin; Clavijo, Laura; Zuluaga, Alejandro; Dal Forno, Manuela; Lumbsch, H. Thorsten (Phytotaxa, 2023)
As a result of botanical and lichenological expeditions in the Colombian Andean-Amazonian Piedmont, in the Brazilian Amazon, and in Veracruz, Mexico, a new species of Sulzbacheromyces was discovered and is here described based on morphological, anatomical, and molecular characters. S. leucodontium differs from other neotropical species in the genus by having white basidiomata and colonial algae in the thallus and represents the species with the widest distribution of the genus in the Americas, from Mexico to Brazil. In addition, the most complete phylogenetic reconstruction of the genus to date is presented as well as a key to the known species of Sulzbacheromyces in the Neotropics.